Qur’anic Ethical Framework for the Use of Artificial Intelligence in Interpersonal Communication: Challenges, Bibliometric Trends, and Strategic Solutions - Muhamad Bisri Mustofa; Siti Wuryan; Fegi Sentiana; Norrodzoh Binti Hj Siren; Abdul Syukur (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract The rapid expansion of Artificial Intelligence (AI) in interpersonal communication has generated complex ethical challenges that remain insufficiently explored from a Qur’anic ethical standpoint. Although existing studies discuss AI ethics broadly, research rarely integrates bibliometric evidence with Islamic moral principles to construct an operational ethical framework. Addressing this gap, this study investigates ethical concerns surrounding AI-mediated communication through a Qur’anic perspective while mapping global research trends to highlight the thematic landscape. Using bibliometric analysis of 220 Scopus-indexed articles, the study identifies major clusters such as Interpersonal Communication, AI Ethics, and Communication Technologies, with the Qur’anic Perspective emerging as an underrepresented yet crucial conceptual bridge. The analysis reveals key ethical issues privacy risks, algorithmic bias, opacity, and the erosion of human trust. As its primary novelty, the study proposes a Qur’anic-based strategic framework that operationalizes the values of justice (‘adl), truthfulness (ṣidq), trustworthiness (amānah), and human dignity (‘izzah) into practical guidelines for AI design and use. This integration offers a normative foundation that can strengthen ethical AI governance within interpersonal contexts. The findings emphasize that responsible AI deployment requires both technological safeguards and value-driven principles to preserve ethical integrity and support humane communication practices. Keywords: Ethical Consideration; AI; Interpersonal Communication; Qur’an.